Noninvasive Treatment of Postpartum Diastasis Recti Abdominis: A Pilot Study. Issue 2 (May 2018) - Tuttle, Lori J.; Fasching, Jennifer; Keller, Allison; Patel, Milan; Saville, Chelsea; Schlaff, Rose; Walker, Alicia; Mason, Maureen; Gombatto, Sara P.
Abstract : Objective: To examine the effectiveness of physical therapy intervention for treating diastasis recti abdominis (DRA) in the postpartum population, with emphasis on transverse abdominis (TRA) exercise and kinesiotaping. Study Design: Pilot randomized controlled trial. Background: DRA may be linked to lumbopelvic and gynecological health problems, and there is limited evidence describing effective noninvasive treatments of DRA in postpartum women. Methods and Measures: Thirty women, 6 to 12 weeks postpartum with a palpable separation of the rectus abdominis muscles (32.03 ± 4.33 years old; number of births = 2.30 ± 1.34), were randomly assigned to TRA exercise intervention (n = 10), kinesiotaping intervention (n = 8), TRA exercise and kinesiotaping combination intervention (n = 5), or control (n = 7). The primary outcome was inter-recti distance (IRD), measured via ultrasound imaging. Secondary outcomes of low back pain and pelvic floor dysfunction were measured via validated questionnaires (Pelvic Floor Distress Inventory [PFDI-20] and Roland-Morris Disability Questionnaire). Data are presented as means ± standard deviation. Results: The largest changes in IRD were observed for the TRA exercise–only and TRA exercise + taping groups. There was no statistical difference in IRD change between the TRA exercise–only and TRA exercise + taping groups. Both groups with TRA exercise components were statistically different from the taping-only group and the control group in IRD change. Conclusions: Based on our preliminary data, exercise targeting the TRA may be an effective treatment method for reducing IRD. Further studies that include a larger patient population, particularly those with low back pain and pelvic floor dysfunction, are needed to replicate these findings and to establish a standardized exercise protocol for DRA.